Recovering bioenergy in Sub-Saharan Africa: gender dimensions, lessons and challenges - Njenga, M.; Mendum, R. (International Water Management Institute, 2018)
There is a strong link between gender and energy in view of food preparation and the acquisition of fuel, especially in rural areas. This is demonstrated in a range of case studies from East and West Africa, where biochar, human waste and other waste resources have been used to produce briquettes or biogas as additional high-quality fuel sources. The synthesis of the cases concludes that resource recovery and reuse for energy offers an alternative to conventional centralized grid projects which, while attractive to investors and large-scale enterprises, do not necessarily provide job opportunities for marginalized communities. Reusing locally available waste materials for energy production and as soil ameliorant (in the case of biochar) in small enterprises allows women and youth who lack business capital to begin modest, locally viable businesses. The case studies offer concrete examples of small-scale solutions to energy poverty that can make a significant difference to the lives of women and their communities.